Hydroxychloroquine Attenuates Myocardial Ischemic and Post-Ischemic Reperfusion Injury by Inhibiting the Toll-Like Receptor 9 – Type I Interferon Pathway - Marsh, Katherine M; Rastogi, Radhika; Zhang, Aimee; Wu, Di; Kron, Irving L; Yang, Zequan (Cardiology and Cardiovascular Medicine, 2022)
Background: We hypothesized that hydroxychloroquine (HCQ) attenuates myocardial ischemia/reperfusion injury (IRI) via TLR9 – type I interferon (IFN-I) pathway inhibition. Methods: The left coronary artery of wild-type (WT) C57BL/6 and congenic TLR9-/- mice was occluded for 40 minutes, with or without 60 minutes of reperfusion (40’/0’ or 40’/60’). Either ODN-2088 or HCQ (TLR9 inhibitors), or ODN-1826 (TLR9 agonist) was administered to determine effect on infarct size (IS). After 40’/0’, cardiac perfusate (CP) was collected from harvested hearts and administered to either intact WT mice after 20 minutes of ischemia or isolated splenocytes. Type-I interferon (IFNα and IFNβ) levels were measured in plasma and splenocyte culture supernatant, and levels of damage associated molecular patterns HMGB1 and cell-free DNA (cfDNA) were measured in CP. Results: After 40’/60’, WT mice treated with HCQ or ODN-2088 had significantly reduced IS. TLR9-/- mice and HCQ-treated WT mice undergoing 40’/0’ and 40’/60’ similarly attenuated IS, with significantly lower IFN-Is in CP after 40’/0’ and in plasma after 40’/60’. IS was significantly increased in 40’/0’ CP-treated and ODN-1826-treated 20’/60’ WT mice. CP-treated WT splenocytes produced significantly higher IFN-I in culture supernatant, which was significantly reduced with HCQ. Conclusions: The TLR9–IFN-I-mediated inflammatory response contributes significantly to both ischemic and post-ischemic myocardial ischemia-reperfusion injury. HMGB1 and cfDNA released from ischemic myocardium activated the intra-myocardial TLR9 – IFN-I inflammatory pathway during ischem